Analisis Kualitas Pelayanan, Kepuasan, Dan Kepercayaan Pelanggan Terhadap Indihome Di Surabaya - Santoso, Yudivan Ilham; kusmayati, nindya kartika; Muslikhun; Kurniawan, Taufik (Universitas Kadiri, 2023)
This study aimed to determine the service quality, satisfaction, and trust of Indihome customers in Surabaya. In this study, researchers used baseline data from customers using the Indihome network. The approach used in this research is the descriptive qualitative method. Interviewing is a technique used to explain research but not to draw more general conclusions. This study used seven respondents living in Surabaya as the research sample. The results of this study are as follows: 1.) Service quality influences the improvement of Indihome services. 2.) Happiness affects improving Indihome services. 3.) Trust has an impact on improving Indihome services. Based on the research results, it is hoped that the company will continue to improve the quality of its services and products so that customers are happier and remain loyal to Indihome products.